2020
DOI: 10.3390/met10030415
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HPT Deformation on the Structure and Properties of Amorphous Alloys

Abstract: Recent studies showed that structural changes in amorphous alloys under high pressure torsion (HPT) are determined by their chemical composition and processing regimes. For example, HPT treatment of some amorphous alloys leads to their nanocrystallization; in other alloys, nanocrystallization was not observed, but structural transformations of the amorphous phase were revealed. HPT processing resulted in its modification by introducing interfaces due to the formation of shear bands. In this case, the alloys af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 117 publications
0
10
0
Order By: Relevance
“…Originally, this SPD method was applied to synthesize porosity-free bulk ultrafinegrained materials with submicron crystallite size [20,24,[26][27][28][29], nevertheless, it has recently become a dominant technique to produce low-porosity metallic glass compacts from amorphous ribbon chips [30,31] and reach large plastic strains in bulk metallic glass alloys (BMGs) [32][33][34]. In a novel paper, it was reviewed that HPT can induce significant plasticity in metallic glasses [35], while nanocrystallization of these alloys can also take place [36]. When HPT is applied to immiscible systems for extreme torsion numbers (N = 1500), new metastable phases can form by mixing the elements on the atomic scale [37].…”
Section: The High-pressure Torsion Proceduresmentioning
confidence: 99%
“…Originally, this SPD method was applied to synthesize porosity-free bulk ultrafinegrained materials with submicron crystallite size [20,24,[26][27][28][29], nevertheless, it has recently become a dominant technique to produce low-porosity metallic glass compacts from amorphous ribbon chips [30,31] and reach large plastic strains in bulk metallic glass alloys (BMGs) [32][33][34]. In a novel paper, it was reviewed that HPT can induce significant plasticity in metallic glasses [35], while nanocrystallization of these alloys can also take place [36]. When HPT is applied to immiscible systems for extreme torsion numbers (N = 1500), new metastable phases can form by mixing the elements on the atomic scale [37].…”
Section: The High-pressure Torsion Proceduresmentioning
confidence: 99%
“…[3,4] Furthermore, the possibility for phase transformations [5][6][7][8] has been shown as well as the evolution of thermodynamically metastable phases such as supersaturated solid solutions [3,9] or amorphous structures, similar to rapid solidification processes. [10] This variety of HPT-induced microstructural evolutions is accompanied by a noteworthy manufacturing advantage. As initial materials for HPT processing, coarse-grained multi-phase alloys, powder blends of different elements or any other combination of solid starting materials can be used.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a number of experiment characterizations and advanced finite element simulations have already been conducted. Gunderov et al studied the microstructural evolution of HPT-processed amorphous alloys and found that the formation of nanocrystallization depends on the chemical composition of alloys and HPT processing regimes [ 17 ]. Additionally, the influence of defects and dislocations on the electro-resistivity of HPT-deformed nickel have been investigated by Korznikova et al [ 18 ].…”
Section: Introductionmentioning
confidence: 99%